Tanya Holland's California soul : recipes from a culinary journey West - Holland, Tanya; Deetz, Kelley Fanto; Hunt, Maria C. (Ten Speed Press, 2022)
"80+ comfort-filled recipes that trace the roots of modern California soul food to the Great Migration that brought African American culture to the West Coast-from the acclaimed chef and author of Brown Sugar Kitchen"--